Post-socialist urban growth of Bucharest, Romania – a change detection analysis on Landsat imagery (1984–2010) - Bogdan Mihai; Constantin Nistor; Gabriel Simion (Acta Geographica Slovenica, 2015)
In this study, Bucharest, the capital city of Romania was selected as a case study. Based on time series of Landsat TM imagery and statistical data, an analysis on urban growth from 1984 to 2010 was performed, using an integrated approach of remote sensing and GIS techniques. The land cover data were validated by CORINE Land Cover maps. The results revealed that rapid urban growth of the Bucharest region led to accelerated land use conversion from cropland to built-up land. The processes of deindustrialization in the core city and industrialization to the ring road represent other driving factors for spatiotemporal pattern of built-up land. The paper will discuss these processes and their impact on economic growth and residential suburbanization of the studied region.